Skye falling : a novel - McKenzie, Mia (Random House, 2021)
"Twenty-six and broke, Skye didn't think twice before selling her eggs and happily pocketing the cash. Now approaching forty, Skye moves through life entirely--and unrepentantly--on her own terms, living out of a suitcase and avoiding all manner of serious relationships. Her personal life might be a mess, and no one would be surprised if she died alone in a hotel room, but at least she's free to do as she pleases. But then a twelve-year-old girl shows up during one of Skye's brief visits to her hometown of Philadelphia, and tells Skye that she's "her egg." Skye's life is thrown into sharp relief and she decides that it might be time to actually try to have a meaningful relationship with another human being. Spoiler alert: It's not easy. Things gets even more complicated when Skye realizes that the woman she tried and failed to pick up the other day is the girl's aunt and now it's awkward. All the while, her brother is trying to get in touch, her problematic mother is being bewilderingly kind, and the West Philly pool halls and hoagie shops of her youth have been replaced by hipster cafes. Told in a fresh, lively voice, this novel is a relentlessly clever, deeply moving portrait of a woman and the relationships she thought she could live without"--